2018
DOI: 10.1097/md.0000000000010301
|View full text |Cite
|
Sign up to set email alerts
|

NUDT15 R139C variation increases the risk of azathioprine-induced toxicity in Chinese subjects

Abstract: Introduction:Azathioprine (AZA) is widely used as an immunosuppressive agent, and its efficacy has been recommended by many clinical studies. However, leukopenia, the most common toxicity, still restricts its clinical applications. Recent studies found that NUDT15 R139C polymorphism is strongly associated with AZA-induced leukopenia in Koreans. However, the follow-up studies available are all limited to inflammatory bowel disease (IBD). Here, we report a case of a Chinese patient with Sjögren syndrome (SS) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Although the association between TPMT polymorphisms and AZA‐induced leukopenia is well‐established, these variants are less common among Asian patients than among White patients, 25,26 and recent studies showed that NUDT15 polymorphisms were associated with thiopurine‐induced toxicity in Asians, including Chinese, Japanese Korean, and Indian populations 5,15,16,27–30 . Preventative screening approaches can be very effective in preventing treatment failure and adverse reactions with severe complications 31,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the association between TPMT polymorphisms and AZA‐induced leukopenia is well‐established, these variants are less common among Asian patients than among White patients, 25,26 and recent studies showed that NUDT15 polymorphisms were associated with thiopurine‐induced toxicity in Asians, including Chinese, Japanese Korean, and Indian populations 5,15,16,27–30 . Preventative screening approaches can be very effective in preventing treatment failure and adverse reactions with severe complications 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between TPMT polymorphisms and AZA‐induced leukopenia is well‐established, these variants are less common among Asian patients than among White patients, 25 , 26 and recent studies showed that NUDT15 polymorphisms were associated with thiopurine‐induced toxicity in Asians, including Chinese, Japanese Korean, and Indian populations. 5 , 15 , 16 , 27 , 28 , 29 , 30 Preventative screening approaches can be very effective in preventing treatment failure and adverse reactions with severe complications. 31 , 32 Our previous studies have shown important clinical implementations of pharmacogenomic testing to prevent severe adverse drug reactions.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Similarly, other studies have also demonstrated an increased risk of thiopurine-induced leukopenia with NUDT15 R139C. 16 - 18 …”
Section: Discussionmentioning
confidence: 93%
“…In meta-analysis studies, TPMT*3C variant is known to be associated with an increased risk in thiopurine-induced leukopenia in European descendants ( Budhiraja and Popovtzer, 2011 ; Avallone et al, 2014 ; Walker et al, 2019 ). On the other hand, NUDT15 R139C (rs116855232, NUDT15*3) variant carriers are strongly associated with thiopurine-induced leukopenia in Asian populations, including Chinese, Japanese, Korean, and Indian populations ( Tanaka et al, 2015 ; Kakuta et al, 2016 ; Moriyama et al, 2016 ; Kim et al, 2017 ; Fei et al, 2018a ; Fei et al, 2018b ; Banerjee et al, 2020 ).…”
Section: Genetic Factors Of Severe Adverse Drug Reactionsmentioning
confidence: 99%